The Effect of Circuit Training and Fartlek Training on the VO₂max of Handball Athletes - Muhammad Fadli; Andi Muhammad Rizky Al Mufarid; Sitti Fatimah Azzahra M; Wilda Yati; Muhammad Rizky Alfarizi (Journal of Physical Education, Sport, and Human Performance, 2025)
This research is an experimental research type that uses a "pre test and post test group design" research design. This research aims to determine; (1) Is there an effect of circuit training on VO2Max of handball athletes; (2) Is there an effect of fartlek training on VO2Max of handball athletes; (3) Is there a difference in the effect of circuit training and fartlek training on VO2Max of handball athletes. The population is all handball athletes. The sample used is 20 handball athletes. The sampling technique is a sample population divided into 2 groups using a block system. The data analysis technique used is descriptive analysis, inferential analysis of the t-test at a significance level of α = 0.05. The results of the study show that; (1) There is an effect of circuit training on VO2Max of handball athletes, with an observation value = -5.093 (Pvalue <0.05); (2) There is an effect of fartlek training on VO2Max of handball athletes, with an observation value = -5.750 (Pvalue <0.05); (3) There is a difference in the effect of circuit training and fartlek training on VO2Max of handball athletes, with tobservation value = 2.205 (Pvalue < 0.05).